Analisis Belajar Keterampilan Motorik - Edil Rohisfi; Neviyarni Neviyarni (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This article discusses the analysis of learning motor skills using references from relevant literature studies, in the concept that learning motor skills is learning by the development of a student's bodily ability which includes gross motoric development and fine motor skills.There are four characteristics of learning motor skills, namely: (1) sequential response, (2) perceptual-motor coordination, (3) response regulation, (4) feedback.Learning motor skills can be divided into three phases or stages, namely (1) the initial or cognitive phase, (2) the fixation or associative phase, and (3) the final or autonomous phase.